2012
DOI: 10.1021/jm301189c
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Discovery of Highly Selective Phosphodiesterase-9A Inhibitors and Implications for Inhibitor Design

Abstract: A new series of phosphodiesterase-9 (PDE9) inhibitors that contain a scaffold of 6-amino-pyrazolopyrimidinone have been discovered by a combination of structure-based design and computational docking. This procedure significantly saved load of chemical synthesis and is an effective method for the discovery of inhibitors. The best compound 28 has an IC50 of 21 nM and 3.3 µM respectively for PDE9 and PDE5, and about three orders of magnitude of selectivity against other PDE families. The crystal structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 48 publications
3
82
0
Order By: Relevance
“…However, in terms of bioavailability and in vivo stability, C33 shows significant improvement over 3r. The oral administration of racemic C33 yielded a C max value of 373 ng/ml and bioavailability of 56.5% (Table 4), in comparison with C max values of 16 and 217 ng/ml and bioavailability of 1.3% and 9.8% for 28s (Meng et al, 2012) and 3r (Shao et al, 2014), respectively. The blood concentration of C33 in the oral administration mode was 113 ng/ml after 6 hours, which is about 19-fold higher than the IC 50 value of 6 ng/ml, indicating practical usability and the potential for C33 as a drug lead.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…However, in terms of bioavailability and in vivo stability, C33 shows significant improvement over 3r. The oral administration of racemic C33 yielded a C max value of 373 ng/ml and bioavailability of 56.5% (Table 4), in comparison with C max values of 16 and 217 ng/ml and bioavailability of 1.3% and 9.8% for 28s (Meng et al, 2012) and 3r (Shao et al, 2014), respectively. The blood concentration of C33 in the oral administration mode was 113 ng/ml after 6 hours, which is about 19-fold higher than the IC 50 value of 6 ng/ml, indicating practical usability and the potential for C33 as a drug lead.…”
Section: Resultsmentioning
confidence: 98%
“…The early studies on the crystal structures of PDE9 in the complex with BAY73-6691 (Wang et al, 2010) and 28s (Meng et al, 2012) showed a small pocket neighboring the inhibitor binding site. This study revealed that the chlorophenyl tail of inhibitor (S)-C33 interacts with the small subpocket that is composed of a portion of helices H14 and H15 and the M-loop, which we thus tentatively named the M-pocket (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several X-ray crystal structures of inhibitors bound to the catalytic domain of PDE9A have been published, providing insight into substrate and inhibitor binding modes and isozyme selectivity profiles [163][164][165][166][167][168]. A mechanism for cGMP hydrolysis was proposed based on PDE9A X-ray crystal structures obtained by a freeze trapping technique [163].…”
Section: Catalytic Domainmentioning
confidence: 99%